TAX AUDIT EFFECTIVENESS AND REVENUE COLLECTION OUTCOMES IN INDONESIA - McMillan, Jim (2024)
This article considers links between Indonesia’s tax collection performance and the design and operation of its tax compliance system, through a study of the tax audit practices and procedures of Indonesia’s tax authority (the Directorate General of Taxation). The article considers the distortionary effect of some features of Indonesia’s tax compliance approach, under which audits tend to be focused largely on taxpayers who are already compliant, and audit activities are narrowly focused and not risk based. The article also considers ways in which Indonesian tax authorities could expand tax audit coverage and modify audit procedures, and thereby increase the effectiveness of their compliance activities in the future, leading to improved revenue collection outcomes.